Manfaat Media Internet Sebagai Sarana Katekese - Edelfrida Taek; Intansakti Pius X (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The development of internet-based social media is very influential in today's life and has really attracted the world so that today many people use internet media as a means of communication. Social communication will be more successful and focused if Catechesis is used as a communication of faith. Therefore, it is necessary to follow the development of Internet media as the media of choice for preaching faith in Jesus Christ. Proclaiming good news in today's modern world must utilize the sophistication of internet media as a means of communicating faith that is not hindered by distance and time. With the existence of internet media such as Facebook, YouTube, WhatsApp, Instagram and TikTok, this is very helpful in preaching faith so that everyone's faith will develop and grow in their daily lives. The purpose of writing this article is to explain how everyone can proclaim the good news about Jesus Christ through internet media. The research was carried out by reviewing the literature regarding forms of online catechesis, namely Online Faith Development (webinar), Online Recollection, and Deepening of the Faith/Holy Scriptures through short videos. And it is hoped that with catechesis via internet media, they can maintain and develop their faith in the Digital Era so that they can have relationships and encounters with others on the internet network.